A novel checkpoint in the Bcl-2–regulated apoptotic pathway revealed by murine cytomegalovirus infection of dendritic cells - Andoniou, Christopher E. (The Rockefeller University Press, 2004)
Infection with murine cytomegalovirus (MCMV) has contributed to understanding many aspects of human infection and, additionally, has provided important insight to understanding complex cellular responses. Dendritic cells (DCs) are a major target for MCMV infection. Here, we analyze the effects of MCMV infection on DC viability, and show that infected DCs become resistant to apoptosis induced by growth factor deprivation. The precise contribution of changes in the expression of Bcl-2 family proteins has been assessed and a new checkpoint in the apoptotic pathway identified. Despite their resistance to apoptosis, MCMV-infected DCs showed Bax to be tightly associated with mitochondria and, together with Bak, forming high molecular weight oligomers, changes normally associated with apoptotic cell death. Exposure of a constitutively occluded Bax NH(2)-terminal epitope was blocked after infection. These results suggest that MCMV has evolved a novel strategy for inhibiting apoptosis and provide evidence that apoptosis can be regulated after translocation, integration, and oligomerization of Bax at the mitochondrial membrane.